Pengaruh Kemampuan, Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan - Deo Sansha Sitorus; Yoyok Soesatyo (Universitas Negeri Surabaya, 2018)
Business development at this time is very tight, this is caused by a number of actors emerging business. To be successful in the business world, companies must pay attention to everything relating to human resources. factors that affect a person's performance is a factor in the organization's ability and motivation factors. In addition, organizational commitment can also support the performance of employees in work. PT Orela Shipyard is a company engaged in the field of shipbuilding projects. PT Orela Shipyard employee population by 51 employees. This study uses the technique of probabilty sampling stratified random sampling as a sampling technique. So there are 45 employees in the sample. The results of this study indicate that the ability to significantly influence employee performance, motivation significant effect on employee performance, and organizational commitment have a significant effect on employee performance. Simultaneously, the ability, motivation and organizational commitment have a significant effect on employee performance.